(untitled) (The Planet, 2024)
Introduction: A volvulus is a twisting or axial rotation of a portion of bowel about its mesentery. In case of Sigmoid Colon volvulus, the term refers to Sigmoid volvulus. Worldwide, colonic volvulus is the third leading cause of large bowel obstruction. Proper diagnosis with appropriate operative approach such as one stage operation (primary resection and anastomosis) two stage operation (Resection and double barrel colostomy, Hartmann’s procedure, primary resection and anastomosis with defunctioning loop ileostomy) is lifesaving. Objective: The aim of this study was to determine the effectiveness of primary resection and anastomosis of acute non complicated sigmoid volvulus in terms of outcome. Methods and materials: It was a randomized control trial study between May 2015 and October 2015. 50 patients were selected by random sampling and were divided into two groups. Group I (experimental group=25) received one stage operation and group II (control group=25) received two stage operation. Results: Two stage operation patients faced 24% stomal complication (bleeding, prolapsed, retraction, parastomal hernia etc.) while one stage operation (primary resection and anastomosis) patients did not experience any late complication (p=0.009). Conclusion: By overall assessment one stage operation was better than two stage operation in context of post-operative wound infection and systemic complications. At two stage operation patient had an inevitable readmission to the surgical indoor for reversal of the stoma which may add post-operative complications and other operative hazards. Hence it can be said that patients with acute non complicated sigmoid volvulus may undergo one stage operation.